2021
DOI: 10.1080/00220620.2020.1868981
|View full text |Cite
|
Sign up to set email alerts
|

Theorising and preparing students for precarity: how can leaders and educators better prepare students to enter an increasingly insecure workforce?

Abstract: Workforce insecurity has significant implications for the role of school leaders and teachers preparing students for changing worlds of work. For educators to better prepare students to enter an increasingly casualised labour workforce, there first needs to be an acknowledgement of how students perceive themselves in relation to post-school life.Drawing on a study of approximately 2500 secondary school students in the Australian state of Victoria, the figure of homo promptus is presented as a figure of youth t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…2. Indeed, while teachers themselves live with precarious employment, their teaching context is equally impacted by students' precarity (Dovemark & Beach, 2016;Walsh & Gleeson, 2021). This uncomfortable being in education creates felt effects across teachers, students, and community (Standing, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…2. Indeed, while teachers themselves live with precarious employment, their teaching context is equally impacted by students' precarity (Dovemark & Beach, 2016;Walsh & Gleeson, 2021). This uncomfortable being in education creates felt effects across teachers, students, and community (Standing, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Educators can adopt the practice of checking for understanding and misconceptions, thereby adjusting instructional methods to suit their students. The educational results will be better as a result [25] .…”
Section: Implement Formative Assessmentsmentioning
confidence: 98%
“…Berntson and Marklund (2007) as well as Kinnunen et al (2011) reported that individuals with high levels of self-perceived employability show better work performance and wellbeing. It is also evident from the literature that the new digital world of work (characterised by rapid forces, digital changes, high unemployment rates, economic challenges and globalisation) negatively influenced graduates' confidence to succeed in finding and maintaining employment (Bezuidenhout, 2011;Walsh & Gleeson, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%